1991
DOI: 10.1159/000186370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dipyridamole on the Short-Term Evolution of Glomerulonephritis

Abstract: The aim of the present study is to evaluate the effect of dipyridamole (300 mg/day) versus placebo in a double-blind randomized trial on membranous glomerulonephritis (M-GMN), mesangial IgA glomerulonephritis (IgA-GMN), and segmentary and focal hyalinosis glomerulonephritis (SFH-GMN) during the first 3 months of treatment. In the case of M-GMN, proteinuria dropped by 60% of the basal value in patients treated with dipyridamole; in the case of IgA-GMN it dropped by 65–70%; and in the case of SFH-GMN it dropped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Anti-proliferative effects on rat mesangial cells have also been reported [8], and, over 15 years ago, Cattell and Mehotra [13] noted that matrix expansion in a rat model of mesangioproliferative glomerulonephritis was also decreased after DP treatment. In addition, several previous studies have shown that DP exerts an anti-proteinuric effect and can reduce the progression of glomerular disease, albeit in small numbers of subjects [14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Anti-proliferative effects on rat mesangial cells have also been reported [8], and, over 15 years ago, Cattell and Mehotra [13] noted that matrix expansion in a rat model of mesangioproliferative glomerulonephritis was also decreased after DP treatment. In addition, several previous studies have shown that DP exerts an anti-proteinuric effect and can reduce the progression of glomerular disease, albeit in small numbers of subjects [14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Mea sures inhibiting mesangial proliferation at any stage of glomerular disease may have important clinical implica tions in delaying the progression of renal disease [1]. Dipyridamole has been reported to be beneficial for patients with glomerulonephritis [21,22], The mecha nism is often thought to be related to its antiplatelet action or hemodynamic effect [23,24]. Dipyridamole has also been shown to decrease mesangial proliferation in either experimental glomerulonephritic models or in human subjects [25,26], Our study may be the first to prove the effect of dipyridamole on mesangial cell proliferation in a cell culture system.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of platelets in the development of renal injury can also be inferred by several studies demonstrating beneficial effects of antiplatelet therapy in glomerulonephritis. Treatment with antiplatelet agents reduced proteinuria in patients with IgAN [15, 16] or MGN [15]. Long-term administration of antiplatelet agents in combination with low dose warfarin retarded the deterioration of renal function in IgAN [17].…”
Section: Discussionmentioning
confidence: 99%